Analisis Fase Preliminary Strategis Sistem Informasi dalam Pengembangan Smart Campus - Fauzi, Cholid; Noviansyah, Beri (Forum Kerjasama Pendidikan Tinggi, 2021)
Smart Campus refers to the integration of the unity of campus life that is supported by technology. The application of Smart Campus is a development from conventional management campus to campus that applies technology, one of the technologies is an information system. For an information system to be successful and optimal, an appropriate strategic information system (SISP) planning is needed in accordance with the business processes of the institution and is used as a blueprint as part of the IT Masterplan for the implementation of the Smart Campus. Smart Campus Strategic Planning implemented by utilizing the Ward and Peppard framework, with identification of information system needs based on the Critical Success Factor (CSF), Value Chain, Gap Analysis and McFarlan Portfolio. The results of this study can be used as a consideration for decision makers to determine campus policies in implementing various services provided by information systems as part of the Smart Campus, which can be described as a campus that intelligently interacts with its academics